PENGARUH CITRA WAHANA PERMAINAN TRANS STUDIO BANDUNG MELALUI KESENANGAN DAN KUALITAS LAYANAN PADA LOYALITAS PELANGGAN - Adhi Widyakto; Endang Tri Widyarti; Kamalina Din Jannah (Faculty of Economics and Business | Universitas Diponegoro, 2020)
The purpose of this study was to examine and analyze the influence of Rides image through delight and service quality to customer loyalty on Transtudio Bandung customers in Jabodetabek. This research is a descriptive study and causal relationship. The sample in this study were 200 respondents. This research method is SEM analysis with Warp PLS tools. The results of this study indicate that waterpark image, delight, and service quality have a significant and positive influence on customer loyalty. Whereas indirectly Rides image influences customer loyalty through delight and service quality.